2011
DOI: 10.1093/jhered/esr090
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Signature of Reproductive Manipulation in the Phylogeography of the Bat Fly, Trichobius major

Abstract: The bat fly (Trichobius major) is a blood-feeding ectoparasite of the cave myotis (Myotis velifer). A recent mitochondrial DNA (mtDNA) study examining population structure of T. major in the South Central United States detected a single haplotype from all individuals examined (N = 48 from 12 different caves), representing one of only a few known examples of such widespread mtDNA uniformity. We examined nuclear genetic diversity using amplified fragment length polymorphism and detected high levels of nuclear ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 72 publications
1
18
1
Order By: Relevance
“…Trowbridge et al (6) documented an Arsenophonus-like bacteria in several fly species belonging to the genus Trichobius (Streblidae, Trichobiinae). This was subsequently corroborated by Lack et al (10) for several populations of Trichobius major and by Nováková et al (11) for an unknown Trichobius species. Arsenophonus spp.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Trowbridge et al (6) documented an Arsenophonus-like bacteria in several fly species belonging to the genus Trichobius (Streblidae, Trichobiinae). This was subsequently corroborated by Lack et al (10) for several populations of Trichobius major and by Nováková et al (11) for an unknown Trichobius species. Arsenophonus spp.…”
mentioning
confidence: 53%
“…Because of limited sampling throughout the known geographic ranges of Basilia and Nycteribia, whether this is truly a replacement rather than a transient infection remains ambiguous, and the frequency of such replacements remains unclear. Streblid endosymbionts identified by Trowbridge et al (6), Lack et al (10), and Nováková et al (11) were previously assigned to the genus Arsenophonus. In our analysis, they form their own, novel monophyletic lineage (clade B), which is distinct from but allied to "Candidatus Riesia pediculicola" (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They belong to the Hippoboscoidea, a group that also encompasses tsetse flies (Glossinidae, see above) and louse flies (Hippoboscidae). Previous studies have identified bacterial symbionts associated with the nycteribiid genera Basilia, Nycteribia, Penicillidia, and Phthiridium (21,28), and the streblid genus Trichobius (31,56). Some of these symbionts are vertically transmitted, and sequences seem to form a monophyletic clade associated with the presumed mutualist bacteria found in sucking lice ("Candidatus Riesia") (37).…”
mentioning
confidence: 99%
“…(i) What is the relationship of bacterial associates in Nycterophiliinae to known bacterial associates in other insects and bat flies? Based on prior evidence from bat flies, it can be expected that Nycterophiliinae harbor bacterial symbionts and that these are likely related to symbionts within the Gammaproteobacteria (21,31,56).…”
mentioning
confidence: 99%